2011
DOI: 10.1364/oe.19.001713
|View full text |Cite
|
Sign up to set email alerts
|

Multiple resonant coupling mechanism for suppression of higher-order modes in all-solid photonic bandgap fibers with heterostructured cladding

Abstract: Abstract:In this paper, we propose a novel mechanism for suppression of higher-order modes (HOMs), namely multiple resonant coupling, in allsolid photonic bandgap fibers (PBGFs) with effectively large core diameters. In an analogy to the well-known tight-binding theory in solidstate physics, multiple anti-resonant reflecting optical waveguide (ARROW) modes bound in designedly arranged defects in the cladding make up Bloch states and resultant photonic bands with a finite effective-index width, which contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Figure 2 shows the fraction of power in the core as a function of wavelength for the FM and two relevant LP 11 -like modes. In the region where the FM couples with the resonators the fraction of core power drops off rapidly, likewise for the first HOM, LP 11 . However the power level of an additional LP 11 -like mode (LP (2) 11 ) increases within the SM bandwidth that is the light blue region in Fig.…”
Section: Results For Original Designmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 2 shows the fraction of power in the core as a function of wavelength for the FM and two relevant LP 11 -like modes. In the region where the FM couples with the resonators the fraction of core power drops off rapidly, likewise for the first HOM, LP 11 . However the power level of an additional LP 11 -like mode (LP (2) 11 ) increases within the SM bandwidth that is the light blue region in Fig.…”
Section: Results For Original Designmentioning
confidence: 97%
“…Furthermore, high refractive index regions operating as resonators in PCFs can be placed in the inner cladding structure. The resonators can couple and create bands of cladding modes, which couple with core modes, whenever index matching is achieved [10,11]. The distributed modal filtering (DMF) rod fiber utilizes resonators in the inner cladding structure to enable SM guidance over a certain spectral range despite the very LMA and ultra low NA [12].…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing scattering phases from individual dielectric elements and the relationship with PBGs are discussed (mostly for telecommunication applications) by Duguay et al (1986), Archambault et al (1993), Rowland et al (2008), and Sakai and Suzuki (2011). These concepts are applied to 2D structures in , Litchinitser et al (2003), Couny et al (2007), and Murao et al (2011). Because Bragg reflectors can be understood through both interference conditions and the PBG condition, their application to acceleration, first explored in Mizrahi and Schachter (2004a), is particularly illuminating, and is discussed in detail in Section III.B.…”
Section: A Photonic Crystalsmentioning
confidence: 99%
“…Liu et al demonstrated the fabrication of a tunable bandpass filter by combining the bend loss edge of an all-solid PBGF and a Bragg fiber [28]. By using multiple resonant coupling method, higher order modes of an all-solid PBGF have been suppressed and the confinement loss of the first bandgap has been increased by applying heterostructured cladding [29]. Moreover, low confinement and bend loss has been obtained for core modes in the first bandgap as well as the higher order bandgaps of an all-solid PBGF [30].…”
Section: Introductionmentioning
confidence: 99%